Antioxidants and biomarkers of oxidative damage in the saliva of patients with Down's syndrome - Sousa, Michelle Cardoso de [UNESP]; Vieira, Rafael Brizola [UNESP]; Santos, Danielle Sá dos [UNESP]; Carvalho, Claudio Antonio Talge [UNESP]; Camargo, Samira Esteves Afonso [UNESP]; Mancini, Maria Nadir Gasparoto Gasparoto [UNESP]; Oliveira, Luciane Dias de [UNESP] (Elsevier B.V., 2015)
Background: The aim of this study was to investigate enzymatic and non-enzymatic antioxidant systems and levels of biomarker levels of oxidative damage in the saliva of patients with Down's syndrome (DS).Methods: Saliva samples were collected from 30 patients with DS and control group (age: 1424 years). Subsequently, the concentrations of superoxide dismutase, concentration of malondialdehyde, carbonylated proteins, uric acid, vitamin C and total protein, peroxidase activity and total antioxidant capacity were analyzed.Results: Patients with DS presented significantly higher concentrations of superoxide dismutase, higher levels of malondialdehyde and salivary total protein content than controls (p < 0.05). Conversely, no difference in carbonylated proteins or antioxidants (uric acid, vitamin C, peroxidase, and total antioxidant capacity) was observed between DS patients and controls (p > 0.05).Conclusion: Patients with DS are more vulnerable to oxidative stress in saliva as indicated by the significant increase in malondialdehyde and superoxide dismutase concentrations found in this study.
Keywords: Down's syndrome; Saliva; Oxidative stress; Antioxidants; Malondialdehyde